READING FOR YOUTH INTEREST DURING CURRENT - Aurelia-Camelia, MARIN; Ionela, POPA (Strategii Manageriale, 2014)
Virtual reality and images conquer them permanently and irrevocably even children from the earliest age. For instance, I can say that as they grow departs books. So many young people arrive at teens refuse to read a book, even electronically. Children considered mandatory reading something imposed by adults and tries to escape, finding other concerns. They also have no motivation, the universe discovered through books hardly seems interesting, which is, in their opinion, obsolete. The environment in which I work led me to satisfy my curiosity namely that of finding out to what extent reading is among the priorities of young people today. This research considers the study of attitudes, behaviors, opinions and intentions of young people their interest in reading, be it physical or books in electronic format. Then I directed a questionnaire to students of the Faculty of Management Marketing in Economic Affairs Rm. Valcea. For example, we chose a target group of young people aged between 18 and 25 years.